Research collaboration with SCUN China - UMP, PNC (Penerbit UMP, 2009)
It was without a doubt a great honour to be appointed as one of the candidates chosen for a 2-week attachment at the South Central University for Nationalities (SCUN) in China under the Universiti Malaysia Pahang (UMP) internationalisation Bearing a responsibility equal to that of acting as ambassador of UMP, Dr.Chin Sim Yee was tasked to find out collaboration opportunities by getting familiarised to SCUN's research and postgraduate studies management systems, infrastructure and facilities - and subsequently to bring to fruition the strategic networking between SCUN and UMP.